MANAJEMEN KINERJA USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Hesti Respatiningsih (FE Program Studi Manajemen, 2019)
Performance management is a part of business management in a modern way, and also applies to small-scale businesses such as Micro, Small and Medium Enterprises (MSMEs). High performance management requires consistent leadership attention. MSMEs need to understand the importance of performance management. This is intended so that in managing its business MSMEs have a way to measure their achievements in implementing strategies to achieve the desired business goals. In addition, the application of performance management can ensure that all resources, systems, and employees provide work results that are in accordance with established business goals Keywords: performance management, leadership, Micro, Small and Medium Enterprises